Nickel-induced magnetic behaviour of nano-structured α-Fe2O3, synthesised by facile wet chemical route. Issue 26 (12th September 2018) - Arodhiya, Sharmila Kumari; Placke, Astrid; Kocher, Jaspreet; Kumar, Ashok; Pechousek, Jiri; Malina, Ondrej; Machala, Libor
ABSTRACT: We report the synthesis of pristine and nickel containing iron oxide (α-Fe2 O3 ) nanocrystallites by facile environmentally benign wet chemical process. The magnetic behaviour of the samples has been found to change progressively with nickel content. The Mössbauer spectra revealed the precipitation of secondary phase of nickel ferrite (NiFe2 O4 ) at ∼2 wt% nickel contents. The transmission electron micrographs together with asymmetric magnetic hysteresis loop have confirmed the formation of core–shell structure. The Morin temperature of nanostructured α-Fe2 O3 as estimated by superconducting quantum interference device has been found to be 257, 245, 247 and 242 K at nickel content of 0, 1, 2 and 4 wt%, respectively. The similar trends of increase/decrease in Morin temperature have been noticed by Mössbauer analysis. Furthermore, below Morin temperature, the temperature range of coexisted antiferromagnetic and ferromagnetic states has been found to increase with increase in nickel content.